Improved epitope resolution of the prefusion trimer-specific antibody AM14 bound to the RSV F glycoprotein. Issue 1 (1st January 2021) - Harshbarger, Wayne; Abeyrathne, Priyanka D.; Tian, Sai; Huang, Ying; Chandramouli, Sumana; Bottomley, Matthew James; Malito, Enrico
ABSTRACT: Respiratory syncytial virus (RSV) is the most common cause of acute lower respiratory tract infections resulting in medical intervention and hospitalizations during infancy and early childhood, and vaccination against RSV remains a public health priority. The RSV F glycoprotein is a major target of neutralizing antibodies, and the prefusion stabilized form of F (DS-Cav1) is under investigation as a vaccine antigen. AM14 is a human monoclonal antibody with the exclusive capacity of binding an epitope on prefusion F (PreF), which spans two F protomers. The quality of recognizing a trimer-specific epitope makes AM14 valuable for probing PreF-based immunogen conformation and functionality during vaccine production. Currently, only a low-resolution (5.5 Å) X-ray structure is available of the PreF-AM14 complex, revealing few reliable details of the interface. Here, we perform complementary structural studies using X-ray crystallography and cryo-electron microscopy (cryo-EM) to provide improved resolution structures at 3.6 Å and 3.4 Å resolutions, respectively. Both X-ray and cryo-EM structures provide clear side-chain densities, which allow for accurate mapping of the AM14 epitope on DS-Cav1. The structures help rationalize the molecular basis for AM14 loss of binding to RSV F monoclonal antibody-resistant mutants and reveal flexibility for the side chain of a key antigenic residue on PreF. This work provides the basis for a comprehensive understanding of RSV F trimer specificity with implications in vaccine design and quality assessment of PreF-based immunogens.